2009
DOI: 10.1002/j.2333-8504.2009.tb02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively Based Assessment Of, For, and as Learning: A Framework for Assessing Reading Competency

Abstract: This paper presents the rationale and research base for a reading competency model designed to guide the development of cognitively based assessment of reading comprehension. The model was developed from a detailed review of the cognitive research on reading and learning and a review of state standards for language arts. A survey of the literature revealed three key areas of reading competency: prerequisite reading skill, model building skill, and applied comprehension skill. Prerequisite reading skill is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 103 publications
(108 reference statements)
0
36
0
Order By: Relevance
“…In the beginning of this paper and elsewhere (Bennett, 2011a(Bennett, , 2011bBennett & Gitomer, 2009;O'Reilly & Sheehan, 2009;Sheehan, & O'Reilly, 2012), we advocate for a different kind of reading comprehension assessment. This new reading assessment is intended to broaden the construct of reading comprehension and promote deeper processing through the use of purpose-driven reading.…”
Section: A Case For Scenario-based Assessmentmentioning
confidence: 85%
See 1 more Smart Citation
“…In the beginning of this paper and elsewhere (Bennett, 2011a(Bennett, , 2011bBennett & Gitomer, 2009;O'Reilly & Sheehan, 2009;Sheehan, & O'Reilly, 2012), we advocate for a different kind of reading comprehension assessment. This new reading assessment is intended to broaden the construct of reading comprehension and promote deeper processing through the use of purpose-driven reading.…”
Section: A Case For Scenario-based Assessmentmentioning
confidence: 85%
“…Put yourself in the head of the test maker, and you score well. While reading in testing situations does in fact represent an authentic and a real purpose for reading (Farr et al, 1990), it grossly underrepresents the full range of reading situations required for college readiness, the workforce, and effective citizenship (McCrudden et al, 2011a,b;O'Reilly & Sheehan, 2009;. Assessing reading comprehension in a traditional and decontextualized manner does not guarantee the scores will apply to other purposeful reading activities, nor does it encourage processing strategies that will ensure flexibility or transfer to situations outside the testing window.…”
Section: Background and Contextmentioning
confidence: 99%
“…CBAL reading summative prototypes have been constructed in keeping with the CBAL reading competency model (O'Reilly & Sheehan, 2009a). That model has three major branches: required skills, reading strategies, and text conventions.…”
Section: Results From Cbal Readingmentioning
confidence: 99%
“…CBAL assessment prototypes use this research to help exemplify and reinforce effective classroom practices for students and teachers. The domain-specific competency models, which synthesize this research and drive the design of CBAL assessment prototypes, can be found in Deane (2011), Graf (2009), andSheehan (2009a).…”
Section: List Ofmentioning
confidence: 99%
“…While existing K-12 summative assessments are generally considered useful for certain purposes, such as rankordering students on a unidimensional scale of reading ability or providing comparative information across groups and in relation to national norms, they have been repeatedly criticized on a number of other counts. These criticisms include, but are not limited to, a narrow or outdated view of the construct, the lack of diagnostic information or inactionable data (e.g., scores given at the end of year when there is no time to adjust instruction), ineffective score reports, weak links to instruction, scant measurement of partial knowledge at the lower end of the distribution, and inadequate tailoring of the assessment to the individual needs of the student Bennett & Gitomer, 2009;Bransford et al, 2000;Chou et al, 2007;Cromley & Azevedo, 2007;Cutting & Scarborough, 2006Francis et al, 2006;Glaser & Silver, 1994;Graesser & Hu, 2012;Guterman, 2002;Hannon & Daneman, 2001;Katz & Lautenschlager, 2001;Keenan, 2012;Magliano et al, 2007;Moran et al, 2008;O'Reilly & Sheehan, 2009;Partnership for 21st Century Skills, 2004;Pellegrino et al, 2001;Rupp et al, 2006;Sheehan & O'Reilly, 2011).…”
Section: Background and Broad Aims Of The Assessment Systemmentioning
confidence: 99%